Hydrologic characterization of the Upper Ayeyarwaddy River Basin and the impact of climate change - Gurung, Pabitra; Dhungana, Shashwat; Kyaw Kyaw, Aung; Bharati, Luna (IWA Publishing, 2022)
This study characterizes the hydrological regime of the Upper Ayeyarwaddy River Basin (UARB) of Myanmar under current and future climate change scenarios by using the Soil and Water Assessment Tool (SWAT). The model simulation results show that the annual precipitation, actual evapotranspiration and water yields are 1,578, 524 and 1,010 mm, respectively. These will increase by 13–28%, 11–24% and 42–198% under two representative concentration pathways (RCPs), RCP 4.5 and RCP 8.5, for the future. There is seasonal variability across the cool, hot and rainy seasons in the agro-ecological regions – mountains, hills and inland plains. As in other Asian regions, the model shows that the wet (rainy) season is becoming wetter and the dry (cool) season is becoming drier in the UARB too.